2019
DOI: 10.1186/s12879-019-4694-8
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii among pregnant women attending antenatal clinics at Hawassa University comprehensive specialized and Yirgalem General Hospitals, in Southern Ethiopia

Abstract: BackgroundToxoplasmosis is caused by infection with the protozoan parasite Toxoplasma gondii. It is acquired by consumption of raw or undercooked meat containing tissue cyst, food or water contaminated with oocyst and congenital infection through the placenta leading to serious congenital abnormalities in the fetus like miscarriage, stillbirth, intrauterine death and neurologic defects. Therefore; this study was aimed to determine the prevalence of toxoplasmosis infection and its possible risk factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
(88 reference statements)
3
17
1
Order By: Relevance
“…This study was showed as the difference in educational status of the study participants have no effect on the seroprevalence, because only 1.8% was heard about Toxoplasmosis even though they were in different educational level and 98.2% doesn't have any information (table 1). This agrees with the study done in Hawassa and Yirgalem Hospitals southern, Ethiopia which indicated as 99.6% of the study participants was no information about Toxoplasmosis [37]. But in reality it is extremely important to increase awareness on the transmission of toxoplasmosis at all level.…”
Section: Discussionsupporting
confidence: 88%
“…This study was showed as the difference in educational status of the study participants have no effect on the seroprevalence, because only 1.8% was heard about Toxoplasmosis even though they were in different educational level and 98.2% doesn't have any information (table 1). This agrees with the study done in Hawassa and Yirgalem Hospitals southern, Ethiopia which indicated as 99.6% of the study participants was no information about Toxoplasmosis [37]. But in reality it is extremely important to increase awareness on the transmission of toxoplasmosis at all level.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, most of the pregnant women in the first, second, and third trimester of their gestation were infected with T gondii , but no significant association was found between seropositivity of anti– T gondii antibodies and gestational ages of the pregnant women, and this is comparable to a finding reported from greater Accra region of Ghana. 44 Contrary to this, 2 studies from Ethiopia by Endris et al 15 and Fenta 45 demonstrated statistically significant positive association between the seroprevalence of T gondii infection and the second and third trimesters of gestational age of pregnancy.…”
Section: Discussionmentioning
confidence: 88%
“…Out of the total of 210 pregnant women, 159 (75.7%) were seropositive for T. gondii, and the odds ratio of having T. gondii infection was high in pregnant women within the age category 36-44 years [58]. A similar study conducted in at Hawassa University comprehensive specialized and Yirgalem General Hospitals in Southern Ethiopia reported a weighted prevalence of 81.8% for the anti-Toxoplasma gondii antibody, and a significant association was observed between seroprevalence and contact with domestic cats [59].…”
Section: Ethiopia Ethiopia Has the Highest Number Of Publications Onmentioning
confidence: 87%